2016
DOI: 10.1515/revneuro-2015-0014
|View full text |Cite
|
Sign up to set email alerts
|

Different patterns of 5-HT receptor and transporter dysfunction in neuropsychiatric disorders – a comparative analysis of in vivo imaging findings

Abstract: AbstractImpairment of serotonin receptor and transporter function is increasingly recognized to play a major role in the pathophysiology of neuropsychiatric diseases including anxiety disorder (AD), major depressive disorder (MDD), bipolar disorder (BD) and schizophrenia (SZ). We conducted a PubMed search, which provided a total of 136 in vivo studies with PET and SPECT, in which 5-HT synthesis, 5-HT transporter binding, 5-HT1 rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 71 publications
2
31
0
Order By: Relevance
“…As a neurotransmitter in the central nervous system, it regulates mood and emotion. However, an imbalance in its functions leads to depression and other neuropsychiatric disorders (Nikolaus, Muller, & Hautzel, ). Despite its vital role in the central nervous system, a majority (95%) of 5‐HT is released in the GI tract by intestinal enterochromaffin cells (Berger et al, ; D. Y. Kim & Camilleri, ) that regulate prokinetic actions, such as gastric emptying, intestinal peristalsis, intestinal secretion, and colonic tone (Berger et al, ).…”
Section: Regulatory Effects On Gastrointestinal (Gi) Motilitymentioning
confidence: 99%
See 1 more Smart Citation
“…As a neurotransmitter in the central nervous system, it regulates mood and emotion. However, an imbalance in its functions leads to depression and other neuropsychiatric disorders (Nikolaus, Muller, & Hautzel, ). Despite its vital role in the central nervous system, a majority (95%) of 5‐HT is released in the GI tract by intestinal enterochromaffin cells (Berger et al, ; D. Y. Kim & Camilleri, ) that regulate prokinetic actions, such as gastric emptying, intestinal peristalsis, intestinal secretion, and colonic tone (Berger et al, ).…”
Section: Regulatory Effects On Gastrointestinal (Gi) Motilitymentioning
confidence: 99%
“…As a neurotransmitter in the central nervous system, it regulates mood and emotion. However, an imbalance in its functions leads to depression and other neuropsychiatric disorders (Nikolaus, Muller, & Hautzel, 2016). Despite its vital role in the central nervous system, a majority Kim & Camilleri, 2000;Wouters, Farrugia, & Schemann, 2007).…”
Section: Signaling Pathways Of Gi Motility Targeted By Pf Extracts mentioning
confidence: 99%
“…Various neurotransmitters have been implicated in the pathophysiology of anxiety and compulsive disorder including dopamine (Plavén Sigray et al, 2016), serotonin (Nikolaus et al, 2016), glutamate (Spencer et al, 2014), and γ-aminobutyric acid (GABA) (Mohler, 2012). A meta-analysis of 1 H magnetic resonance spectroscopy (MRS) reported that no significant differences in GABA levels were found in panic disorder patients (Schür et al, 2016) while the GABA(A) receptor was reported to decrease throughout the mesolimbocortical system in anxiety disorder (Nikolaus et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These psychedelic effects of psilocybin are mediated primarily by its actions as an agonist at the serotonin 2A receptor (5‐HT 2A R) (Vollenweider, Vollenweider‐Scherpenhuyzen, Babler, Vogel, & Hell, ). The 5‐HT 2A R is an excitatory 5‐HT receptor in the human brain most highly expressed throughout the cerebral cortex (Beliveau & Ganz, ; Varnas, Halldin, & Hall, ), and dysfunction of 5‐HT 2A R is implicated in neuropsychiatric disorders including depression and schizophrenia (Albert, Benkelfat, & Descarries, ; Bhagwagar et al, ; Lin, Jiang, Kan, & Chu, ; Naughton, Mulrooney, & Leonard, ; Nikolaus, Muller, & Hautzel, ). It is therefore possible that 5‐HT 2A R‐mediated effects of psilocybin and other psychedelics contribute to enduring increases in trait Openness.…”
Section: Introductionmentioning
confidence: 99%